The Digital Prescription: FDA-Approved Digital Therapeutics for Chronic Disease Management - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of healthcare is undergoing a profound transformation, driven by the convergence of clinical science and advanced technology. At the forefront ...
Keywords: Drug Discovery; Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care